Avaliação do feito citoprotetor da amifostina na cardiotoxicidade aguda induzida por doxorubicina - Freire, Rosemayre Souza (2008)
Doxorubicin (DOX) is an antineoplasic anthracyclic agent used on the treatment of several solid tumors and hematological cancers. DOX-induced cardiotoxicity has been studied for decades as a limiting factor on the anticancer therapy with this drug. Despite the current knowledge concerning the mechanisms of DOX-induced cardotoxicity, its pathophysiology is still not clear. Purpose: To evaluate of the amifostine and glutathione citoprotective effect on the DOX-induced acute cardiotoxicity and to study the morphology of cardiac tissue through the use of atomic force microscopy as a tool. Materials and Methods: C57BL/6 female mice were treated with doxorubicin (25mg/Kg i.p.) or saline (0,2mL i.p.) and sacrificed 96 hours after treatment. In another experimental setting, mice were given amifostine (AMF 25, 50 e 100 mg/Kg s.c.), glutathione (GLT 125, 250 e 500mg/Kg s.c.) or vehicle, 30 mim before the administration of DOX, except glutathione that was injected daily. Analitical parameters included: electrocardiograms, cardiac and spleen indices, non protein suphidrils groups levels, CK and CK-MB cardiac enzymes levels, histological analysis, cardiac levels of (TNF-, IL-1, iNOS) determined by ELISA, immunohistochemistry for TNF-, IL-1, iNOS, apoptosis and atomic force microscopy tissue analysis. Results: AMF (100mg/Kg) and GLT (250 e 500 mg/Kg) treatments were able of improve the survival rate of animals in spite of the injection of DOX (25 mg/Kg) in comparison to DOX-treated only group (p<0.05). A AMF e GLT were also able to prevent electrocardiographic changes (rising of QRS e QTc and reduced R amplitude), changes in the cardiac and spleen indices, the augmentation of blood levels of CK e CK-MB, reduction of non proteic suphidrils groups levels, and histological changes induced by DOX (25mg/Kg). DOX induced the augmentation of the immunostaining for apoptotic cells and iNOS what was prevented by the administration of amifostine. The atomic force microscopy reveals morphological changes on the tissue organizational structure which is not possible to be observed through optical microscopy. Conclusion: Our results suggest that the amifostine citoprotective effect on DOX-induced acute cardiotoxicity is due the rising of glutathione peroxidase activity in the cardiac tissue. The citoprotective effect of amifostine is as efficient as the reference drug dexrazoxane. The use of atomic force microscopy as a new pharmacological tool for comparative analysis in nanometric scale allow us to observe DOX-induced membrane destruction what is suggestive of oxidative stress process.